1997
DOI: 10.1111/j.1442-2042.1997.tb00134.x
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Life Survey of Urinary Diversion Patients: Comparison of Continent Urinary Diversion Versus Ileal Conduit

Abstract: Background: Continent urinary reservoirs (CUR) have become one of the major options for patients requiring urinary diversion to improve their quality of life (QOL). To assess whether CUR enhanced postoperative QOL, we surveyed patients with CUR and ileal conduit (IC) using a questionnaire sent by mail. Patients and Methods:The questionnaire consisted of 133 questions that covered physical and mental status, social life, sexual habits and symptoms related to urinary diversions. A total of 172 questionnaires wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
27
0
1

Year Published

2002
2002
2015
2015

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 7 publications
1
27
0
1
Order By: Relevance
“…8 The questionnaire consisted of 35 questions divided into functional (physical, role [work situation], social and financial, emotional, cognitive, overall health), general (pain, fatigue, sleep disturbance, nausea and vomiting, constipation, diarrhea), and urinary diversion-related symptom categories (Appendix I). The questionnaire had five items relating to physical condition, two relating to role, three relating to social and financial interaction, five on mental condition, one on cognition, 12 on general symptoms, five on urinary diversion-related symptoms and two relating to overall health.…”
Section: Quality Of Life Measurementmentioning
confidence: 99%
See 1 more Smart Citation
“…8 The questionnaire consisted of 35 questions divided into functional (physical, role [work situation], social and financial, emotional, cognitive, overall health), general (pain, fatigue, sleep disturbance, nausea and vomiting, constipation, diarrhea), and urinary diversion-related symptom categories (Appendix I). The questionnaire had five items relating to physical condition, two relating to role, three relating to social and financial interaction, five on mental condition, one on cognition, 12 on general symptoms, five on urinary diversion-related symptoms and two relating to overall health.…”
Section: Quality Of Life Measurementmentioning
confidence: 99%
“…We modified two items in the EORTC QLQ-C30 and the questionnaire ordering, and added five items referring to urinary diversion-related symptoms of the QOL survey of Okada et al . 8 To assess the postoperative health-related QOL of IRB, we carried out a survey comparison of IRB patients and ileal conduit (IC) patients using this questionnaire sent by mail.…”
Section: Introductionmentioning
confidence: 99%
“…Several prior studies have found that patients treated with orthotopic continent diversion are more likely to travel, to engage in leisure activities and to suffer fewer social deficits than those managed with incontinent diversions. 19,22,[30][31][32] Others have found that urinary leakage is a greater concern among patients treated with ileal conduit, compared with continent diversion, 14,33,34 which may contribute to less social behaviour.…”
mentioning
confidence: 99%
“…22 Even so, each type of urinary diversion is associated with a different set of well-described treatment-related effects. In those managed with ileal conduit, concern centres…”
mentioning
confidence: 99%
See 1 more Smart Citation